Integration of Open Metal Sites and Lewis Basic Sites for Construction of a Cu MOF with a Rare Chiral Oh‐type cage for high performance in methane purification. Issue 50 (19th February 2018) - Meng, Lingkun; Niu, Ziyuan; Liang, Chen; Dong, Xinglong; Liu, Kang; Li, Guanghua; Li, Chunguang; Han, Yu; Shi, Zhan; Feng, Shouhua
Abstract: A Cu metal‐organic framework (MOF), [Cu4 (PMTD)2 (H2 O)3 ]⋅ 20 H2 O, 1, (where PMTD is 1, 4‐phenylenebis(5‐methyl‐4 H ‐1, 2, 4‐triazole‐3, 4‐diyl)bis(5‐carboxylato‐3, 1‐phenylene)bis(hydroperoxymethanide)), with a rare chiral O h ‐type cage, and dual functionalities of open metal sites and Lewis basic sites, based on a designed U‐shaped ligand, was synthesized by hydrothermal methods. It exhibits high CO2, C2, and C3 hydrocarbon storage capacity under atmospheric pressure, as well as high H2 (1.96 wt.%) adsorption capacity at 77 K. Methane purification capacity was tested and verified step by step. Isosteric heats ( Q st ) studies reveal that CH4 has the weakest van der Waals host–guest interactions among the seven gases at 298 K. Ideal adsorbed solution theory (IAST) calculation reveals that compound1 is more selective toward CO2, C2 H6, and C3 H8 over CH4 in further calculating its separation capacity, as exemplified for CO2 /CH4 (50:50, 5:95), C2 H6 /CH4 (50:50, 5:95), or C3 H8 /CH4 (50:50, 5:95) binary gas mixtures. Breakthrough experiments show that1 has a significantly higher adsorption capacity for CO2, C2 H6, and C3 H8 than CH4 . The selective adsorption properties of1 make it a promising candidate for methane purification. Abstract : Gassed up : A Cu MOF, with dual functionalities and rare chiral O h ‐type cage has been designed and synthesized for methane purification. The MOF exhibits high adsorption capacity for seven C1, C2, and C3 hydrocarbons and little adsorption for methane. Isosteric heats ( Q st ) reveals that CH4 has the weakest van der Waals host–guest interactions. Ideal adsorbed solution theory (IAST) calculation and breakthrough experiments testify that the Cu MOF is a promising candidate for methane purification.